Factors Affecting People's Participation and Implementation of Institution-Village Linkage Programme in Sunderbans,West Bengal - Aparna Roy, Sujeet K. Jha, (Indian Journal of Extension Education, 2022)
Institution -Village Linkage Programme (IVLP) was conceived of the philosophy of participatory research in the technology generation process. entral Soil Salinity Research Institute implemented IVLP in two villages of Sunderban . Several factors affect people's participation in any development programme. Extent of people's participation in IVLP programme was moderate. otivational factors, social credibility of the programme, family support, need for information, input etc. promote people's participation in IVLP for infusing The C s Ahigh degree of participation is not usually possible from the outset. The study revealed that m d .